Effectiveness of E-Modules based on Inquiry Model Integrated with SETS Approach on 21st Century Skills - Westi Widia Wati; Syafriani Syafriani (Journal of Innovation in Educational and Cultural Research, 2023)
The goal of this project is to create a successful physics e-module for 21st-century skills, utilizing an inquiry model combined with the SETS approach. The method used was the reference approach to Research and Development. This research was Plomp's (1997) development model. Seventy high school students served as the study's subjects. Results of an e-module effectiveness test for collaboration and critical thinking skills make up the data collected for this study. The control class's average score for critical thinking abilities was only 51.15 with a sufficient category, whereas the experimental class's score was 79.38 with a high category for each indicator. The results of the critical thinking skills were also strengthened by conducting the N-gain test. The control class had an n-gain value of -0.37 with a low category, while the experimental class had an n-gain value of 0.58 with a medium category. The experimental class's average student collaboration skills were 84.02 in the very collaborative category, compared to 76.12 in the collaborative category for the control group. These results indicate that the physics e-module is useful in enhancing students' 21st-century abilities.